2016
DOI: 10.1542/peds.2015-2091
|View full text |Cite
|
Sign up to set email alerts
|

Presumed Pseudotumor Cerebri Syndrome After Withdrawal of Inhaled Glucocorticoids

Abstract: Pseudotumor cerebri syndrome (PTCS) is characterized by increased intracranial pressure with normal brain parenchyma and cerebrospinal fluid constituents. PTCS after withdrawal of systemic corticosteroids also has been described in children. In contrast, to our knowledge, PTCS after withdrawal of inhaled glucocorticoids has not previously been described. Here we report the case of an 8-year and 6-month-old girl who developed signs and symptoms consistent with PTCS after withdrawal of inhaled glucocorticoids. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…3,26 Short courses of steroids can be used as a bridge to the treatment of pseudotumor cerebri syndrome in fulminant disease, likely acting to reduce papilledema. However, this clinical scenario as well as previous reports of pseudotumor cerebri onset following withdrawal of systemic and inhaled steroids 27 -29 suggests that lack of steroids might inversely promote pseudotumor cerebri. Thus, steroids may play a more central role to pseudotumor cerebri syndrome pathophysiology than previously believed.…”
Section: Discussionmentioning
confidence: 62%
“…3,26 Short courses of steroids can be used as a bridge to the treatment of pseudotumor cerebri syndrome in fulminant disease, likely acting to reduce papilledema. However, this clinical scenario as well as previous reports of pseudotumor cerebri onset following withdrawal of systemic and inhaled steroids 27 -29 suggests that lack of steroids might inversely promote pseudotumor cerebri. Thus, steroids may play a more central role to pseudotumor cerebri syndrome pathophysiology than previously believed.…”
Section: Discussionmentioning
confidence: 62%
“…We found that prophylactic dexamethasone was able to prevent IIH symptoms that would otherwise consistently appear in the infant patient following HD-MTX. This is a surprising finding when compared to previous research that showed corticosteroids used for treatment of autoimmune diseases like JIA and Crohn's disease could cause IIH after prolonged use in children and adults (Friedman et al, 2014;Kwon et al, 2016). There is a paucity of pediatric data to guide the use of medications in IIH, so there is much debate surrounding treatment of IIH in children.…”
Section: Discussionmentioning
confidence: 76%
“…[ 11 29 ] Similarly, steroids administration was reported by a small portion of our study participants. Although the evidence does not support the presence of a correlation between steroids use and IIH,[ 30 ] previous studies reported that steroids withdrawal is significantly correlated,[ 31 ] which can be explained by the induced adrenocortical insufficiency. [ 32 ]…”
Section: Discussionmentioning
confidence: 97%